2023
DOI: 10.1111/fwb.14068
|View full text |Cite
|
Sign up to set email alerts
|

Nanoplastics modulate the outcome of a zooplankton–microparasite interaction

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 132 publications
0
2
0
Order By: Relevance
“…Physiological characteristics suggested terrestrial origin of yeast and are adapted to marine ecosystems. A recent study on nanoplastics by Mavrianos et al (2023) showed how plastic pollution affects the infection of yeast in diverse ways. There was an increase in the proportion of host infection under plastic exposure, whereas, reduced disease prevalence was observed due to increase in host mortality under higher plastic concentration.…”
Section: Mps Increase Disease Prevalencementioning
confidence: 99%
“…Physiological characteristics suggested terrestrial origin of yeast and are adapted to marine ecosystems. A recent study on nanoplastics by Mavrianos et al (2023) showed how plastic pollution affects the infection of yeast in diverse ways. There was an increase in the proportion of host infection under plastic exposure, whereas, reduced disease prevalence was observed due to increase in host mortality under higher plastic concentration.…”
Section: Mps Increase Disease Prevalencementioning
confidence: 99%
“…Furthermore, Mavrianos et al [ 80 ] analyzed microplastic impacts individually and integrated with microparasites Metschnikowia on zooplankton health. It was revealed that a shortened life period and reproduction were observed.…”
Section: Zooplankton and Microplastics In Lab Studies: Assessing Haza...mentioning
confidence: 99%